A DNA‐Encoded FRET Biosensor for Visualizing the Tension across Paxillin in Living Cells upon Shear Stress. Issue 1 (2nd November 2021) - Shao, Shuai; Deng, Sha; Jiang, Qingyun; Zhang, Hangyu; Zhang, Zhengyao; Li, Na; Cong, Fengyu; Tiihonen, Timo; Liu, Bo
Abstract: Paxillin is a potential participant in direct intracellular force transmission, which is considered as the foundation of cells sensing and responding to the extracellular environment. However, the detection of tension across paxillin has not been achieved due to lacking microsized tools. Herein, a paxillin tension sensor (PaxTs) based on the Fluorescence Resonance Energy Transfer (FRET) technique was constructed. PaxTs can be expressed and assembled to FA sites spontaneously to visualize the tension across paxillin with FRET efficiency of ∼62.4 % in living cells. The tension across paxillin was found to decrease upon shear stress, in which the membrane fluidity and contractility of actin acted as cushions. It is observed that paxillin participates in the pathway of cell membrane‐cytoskeleton‐FAs for force transmission upon mechanical force in real time visualization, which provides a promising new method to investigate the direct intracellular force transmission in biology and technology. Abstract : Visualizing the tension across paxillin in real time : This work provides a DNA‐encoded biosensor based on a Fluorescence Resonance Energy Transfer(FRET) technique to detect the tension across paxillin in living cells. The results indicate that there exists a force transmission pathway described as 'membrane‐cytoskeleton‐FAs' and involved with paxillin upon mechanical force.